Korelasi Experience Marketing, Emotional Engagement, dan Brand Image Terhadap Re-Visit Intention di The Allure Ubud Villa - Ulandari, Komang; Maheswari, Anak Agung Istri Agung; Basmantra, Ida Nyoman; Sari, Putu Ratna Juwita (Masyarakat Ekonomi Syariah Bogor, 2025)
This research endeavor seeks to elucidate the partial and simultaneous impacts of experiential marketing, emotional marketing, and brand equity on the likelihood of re-invitation. The population under investigation consisted of 93 patrons who had previously resided at The Allure Ubud Villa. The methodologies employed for data analysis encompassed Validity Testing, Reliability Testing, Classical Assumption Testing, Multiple Linear Regression Analysis, Coefficient of Determination Testing, F-Testing, and t-Testing. The findings indicated that experiential marketing exerted a positive and statistically significant influence on re-invitation, emotional marketing similarly demonstrated a positive and statistically significant effect on re-invitation, and brand equity also exhibited a positive and statistically significant influence on re-invitation. The recommendation proffered by the researcher is that The Allure Ubud Villa should enhance the competencies of its staff in delivering amicable service, by providing training, always providing good service, complete facilities, so that later guests who stay are truly immersed in the experience during their stay, always supervise employees in providing service, so that employees strive to provide the best service, and strive to build emotional attachment to guests who stay, by always providing and paying attention to guests.